(untitled) (Philological Studies, 2019)
As it is well known, the science of style is a science that studies expressive means and language possibilities as well as their realization in the speech. Expressive means and language possibilities may be considered at all levels, and their realization may appear in spoken and written form, with different features. The review of expressive means and language possibilities creates conditions for occurrence of objective or individual stylistics. In that regard our attempt is to recognize the subjective or individual style of the linguistic expression of the author in texts with scientific and functional style. Our attempt in this study is to distinguish the individual linguistic expression in the works of Blaze Koneski, Radmila Ugrinovska-Skalovska and Blagoja Korubin. In addition to Koneski’s texts included in the scientific and artistic-literary functional style, Ugrinovska-Skalovska and Korubin’s texts fall under scientific and functional style. Through examples we tried to emphasize the individual linguistic aspect of each of them, whereupon by way of analysis we established that in the linguistic expression in the texts with scientific and functional style we may speak about distinguishable characteristics of the author’s expression. Individual/author’s characteristics are not presented as “independent” in a functional style, which is established by the examples of Koneski’s linguistic expression that can be also perceived in the artistic-literary style. By their distinction we may speak about the author’s stylish characteristic.